2010
DOI: 10.1074/jbc.m109.026203
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transport Chain-dependent and -independent Mechanisms of Mitochondrial H2O2 Emission during Long-chain Fatty Acid Oxidation

Abstract: Oxidative stress in skeletal muscle is a hallmark of various pathophysiologic states that also feature increased reliance on long-chain fatty acid (LCFA) substrate, such as insulin resistance and exercise. However, little is known about the mechanistic basis of the LCFA-induced reactive oxygen species (ROS) burden in intact mitochondria, and elucidation of this mechanistic basis was the goal of this study. Specific aims were to determine the extent to which LCFA catabolism is associated with ROS production and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
175
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(188 citation statements)
references
References 73 publications
11
175
2
Order By: Relevance
“…A stronger candidate is the ETF system (ETF and ETFQOR) because it has been implicated in superoxide/H 2 O 2 production in skeletal muscle (54). 3 Several lines of evidence do not support a role for it in what we define as mGPDH-specific superoxide production.…”
Section: Discussionmentioning
confidence: 92%
“…A stronger candidate is the ETF system (ETF and ETFQOR) because it has been implicated in superoxide/H 2 O 2 production in skeletal muscle (54). 3 Several lines of evidence do not support a role for it in what we define as mGPDH-specific superoxide production.…”
Section: Discussionmentioning
confidence: 92%
“…Palmitate-induced oxidative stress has been reported to contribute to insulin resistance in H4IIEC3 rat hepatocytes [40] . Fatty acid accumulation stimulates ROS generation in the liver presumably due to enhanced β-oxidation and to the consequent electron overflow in the mitochondrial electron transfer chain [41] ( Figure 2B). However, a decrease in mitochondrial quinone pool and a related inhibition of mitochondrial oxidative metabolism were also suggested to underlie the increased mitochondrial ROS production in high fat diet [42] .…”
Section: Lipotoxic Oxidative Stressmentioning
confidence: 99%
“…The latter situation is suggested to be the most physiologically relevant ROS production in mammals (Miwa & Brand, 2003). Recent work from Seifert et al (2010) showed that LCFA β-oxidation is associated with enhanced ROS production, through a mechanism involving complex III, the electron transfer flavoprotein (ETF) and ETF-oxidoreductase.…”
Section: Mitochondrial Production Of Reactive Oxygen Species and Cellmentioning
confidence: 99%
“…Similarly, a small decrease in membrane potential deeply reduces ROS production (Votyakova & Reynolds, 2001). Therefore mild uncoupling resulting from a small decrease in membrane potential is considered as a natural antioxidant process (Seifert et al, 2010;Skulachev, 1997). However, not all sites of ROS production are sensitive to membrane potential.…”
Section: Mitochondrial Production Of Reactive Oxygen Species and Cellmentioning
confidence: 99%
See 1 more Smart Citation